2013
DOI: 10.1007/s00405-013-2638-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size measured by preoperative ultrasonography and postoperative pathologic examination in papillary thyroid carcinoma: relative differences according to size, calcification and coexisting thyroiditis

Abstract: Ultrasonography (US) is a useful diagnostic modality for evaluation of the size and features of thyroid nodules. Tumor size is a key indicator of the surgical extent of thyroid cancer. We evaluated the difference in tumor sizes measured by preoperative US and postoperative pathologic examination in papillary thyroid carcinoma (PTC). We reviewed the medical records of 172 consecutive patients, who underwent thyroidectomy for PTC treatment. We compared tumor size, as measured by preoperative US, with that in pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A subgroup analysis of 34 PTMCs revealed no significant differences; however, 18.8% of nodules that measured larger than 1 cm on USG were found to be smaller than 1 cm on pathology [ 18 ]. Yoon et al [ 19 ] included 172 PTCs (100 PTMCs) in their study and found that the pathologic tumor size was 10% smaller than the sonographic size. Hahn et al [ 15 ] studied 490 PTCs (272 PTMCs) and observed that preoperative USG tended to overestimate the size of tumors, especially those smaller than 1.0 cm.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup analysis of 34 PTMCs revealed no significant differences; however, 18.8% of nodules that measured larger than 1 cm on USG were found to be smaller than 1 cm on pathology [ 18 ]. Yoon et al [ 19 ] included 172 PTCs (100 PTMCs) in their study and found that the pathologic tumor size was 10% smaller than the sonographic size. Hahn et al [ 15 ] studied 490 PTCs (272 PTMCs) and observed that preoperative USG tended to overestimate the size of tumors, especially those smaller than 1.0 cm.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, however, both benign and malignant thyroid nodules with diverse histologic diagnoses were included in the study population. Yoon et al [ 10 ] reported that papillary carcinoma sizes measured postoperatively were consistently significantly smaller than the US-estimated sizes, with a mean percentage difference of 9.9%. However, although they evaluated differences in the size of the individual tumors measured by preoperative US and postoperative pathology, they did not assess the significance of agreement between the measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…We recently read with interest an article ''Tumor size measured by preoperative ultrasonography and postoperative pathologic examination in papillary thyroid carcinoma: relative differences according to size, calcification and coexisting thyroiditis'' [1], published in European Archives of Oto-Rhino-Laryngology. To begin with, we appreciate the authors' efforts paid in this original article.…”
Section: Respected Editormentioning
confidence: 99%